SISTEM TELEMETRI SIMULASI MITIGASI BENCANA KEGEMPAAN DAN DETEKSI PENINGKATAN KADAR KONDUKTIVITAS BELERANG PADA GUNUNG BERAPI BERBASIS WIRELESS 802.15.4 - P, Yuhananisa; PN, Yayan; K, Lailatul; L, Rahil; SP, Wahyu; O, Ria (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2014)
Laboratory studies on disaster simulation systems telemetry was conducted focusing on some part of the parameters to determine the character of the natural phenomena that occur. Parameters measured were conductivity levels of sulfur in marine volcanic and earthquake intensity. The technique is to do with the design of instrumentation tool by using vibration sensor meas vibration sensors and sensor electrode conductivity copper as sulfur. Data obtained using a telemetry system transmitted by the wireless XBee are working on 802.15.4 protocol. The data have been sent in the form of analog data is converted to digital analogue converter (ADC). The parameters controlle in this simulation is the liquid volume of 10 ml, and the temperature room was 32° C and humidity of 73%. The results of data sent to the recipient noted that the major instrument for the conductivity amounted to 0.01361 K?-1 in 0 gmass. The data 5.011 g to 20.002 g are having conductivity between 0.01000 K?-1 to 0.01418 K?-1. The data result of Vibration sensor at 0 g to 20 002 g, have voltages ammounted2.752 volts, worth voltage increases to 3.724 volts.